2021
DOI: 10.1093/jscr/rjab450
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the posterior cortex of the sternum during resection of a superficial anterior chest wall sarcoma

Abstract: Following resection of a sternal tumor, respiratory dysfunction can occur and rigid reconstruction is necessary. An 82-year-old woman noted a mass in the anterior chest wall that was increasing in size. The tumor was located on the left aspect of the sternum at the level of the third rib. A radiation-induced malignant spindle cell tumor was diagnosed because of a history of irradiation for hilar lymph node carcinoma. The tumor was resected with the surrounding tissues of the second-to-fourth ribs and sternum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Previous reports of similar uses are seen in the literature for a use case in osteosarcoma resection of the femur [ 7 ]. Another case was reported in the literature regarding sarcoma resection in the sternum in crucial areas [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports of similar uses are seen in the literature for a use case in osteosarcoma resection of the femur [ 7 ]. Another case was reported in the literature regarding sarcoma resection in the sternum in crucial areas [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another case was reported in the literature regarding sarcoma resection in the sternum in crucial areas [8].…”
Section: Figure 8: Demonstration Of Sashimi Technique and Use Case De...mentioning
confidence: 99%
“…Partial sternectomies are reserved for more localized tumors ( 4 ). Some authors ( 35 ) have even reported more conservative approaches with preservation of the posterior cortex of the sternum, but in our opinion, since an R0 resection is necessary to avoid the high risk of tumor recurrence and since these supposedly limited resections frequently include skin, soft tissue or ribs excision, its advantages are highly questionable.…”
Section: Strategies For Resectionmentioning
confidence: 92%